SH3KBP1 Promotes Glioblastoma Tumorigenesis by Activating EGFR Signaling - Song, Hai; Wang, Yanpei; Shi, Chaojia; Lu, Jianxiang; Yuan, Tian; Wang, Xiangpeng (Frontiers in Oncology, 2021)
Glioblastoma (GBM) is the most common and aggressive brain tumor. Activation of epidermal growth factor receptor (EGFR) occurs in various cancers and promotes tumor progression. In this study, we reported that both SH3-domain kinase binding protein 1 (SH3KBP1) mRNA and protein levels are elevated in GBM and its high expression predicts worse survival of GBM patients. In addition, SH3KBP1 was prominently expressed in GBM stem cells. Targeting SH3KBP1 expression dramatically impairs GBM cell proliferation, migration and GSCs self-renewal abilities in vitro and xenograft tumors growth in vitro. Moreover, we found that SH3KBP1 directly interacts with EGFR and acts as adaptor protein to transduce EGFR signaling. Together, our work uncovers a critical function for SH3KBP1 and provides insight into new prognosis marker and therapeutic target in GBM.